The Positive Effect of Creative Movement Model on Children’s Personal Skills - Dewi, Putu Sinta; Antara, Putu Aditya; Ujianti, Putu Rahayu (Universitas Pendidikan Ganesha, 2020)
As the importance of personal skills stimulation for children to prepare and equip children in facing various learning levels of further education is necessary, research about it is needed. This study examined the effect of creative movement model on the personal skills of early childhood. This study used a quasi-experimental approach with post-test only control group design. The population of this study was students of Group B Cluster III Kindergarten in Payangan District, Gianyar which the sample was Melati Kindergarten as an experimental group with treatment and Hindu Widya Kumara Santhi Kindergarten as a control group without treatment. Data analysis of the study was descriptive statistics and inferential statistics, by using t-test that was processed by IBM SPSS Statistics ver. 24 for Windows. The result of data interpretation in hypothesis test showed that Sig. (2-tailed) score was 0.001 which meant the significance score was smaller than α (0.001 <0.05). According to these statements, it could be concluded that Ho was rejected and Ha was accepted. The study demonstrates that creative movement model has positive effect on children’s personal skills. With this finding, parents and especially educators expected to be willing to develop various creative movement activities that can stimulate children's personal skills more optimally and sustainably. The benchmarks of children's achievement should go beyond cognitive aspects; thus, teachers need to provide stimulation for children's personal skills to develop social emotional aspect.